PENGARUH CORPORATE GOVERNANCE DAN MANAJEMEN ASET TERHADAP KINERJA KEUANGAN - Mulyani, Tri; Nazar, Shinta Ningtiyas (Jurnal Nusa Akuntansi, 2025)
This study aims to determine and provide empirical evidence regarding the influence of corporate governance and asset management on financial performance in financial sector sub-sector banks companies listed on the Indonesia Stock Exchange in 2020-2022. This study uses secondary data in the form of annual financial reports from the Indonesia Stock Exchange (IDX). The population in this study is financial sector sub-sector banks companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique in this study used the purposive sampling method and obtained 16 companies with a time span of 3 years, so that the data processed was 48 data samples. The data analysis technique in this study uses the multiple linear analysis method and the data analysis tool in this study uses the Eviews software program version 12. The results of the study indicate that corporate governance proxied by an independent board of commissioners, managerial ownership, and audit committee and asset management simultaneously have a significant effect on financial performance. An independent board of commissioners does not affect financial performance. Managerial ownership does not affect financial performance, The audit committee does not affect financial performance. Asset management has a positive and significant effect on financial performance.